(untitled) (Annals of Medical Research, 2022)
Aim: In our study, it was aimed to present our retrospective clinical and radiological short and medium-term results in patients who underwent total knee prosthesis and compare them with the literature. Materials and Methods: 74 knees of 55 patients who were followed-up regularly from 114 patients who underwent primary ligament-cutting cementitious total knee prosthesis between January 2015 and 2020 in the Department of Orthopedics and Traumatology of our clinic were included in this study. Our study is a retrospective study, and our patients were evaluated clinically according to the American Knee Society scoring system before and after surgery, while they were evaluated radiologically according to the Total Knee Replacement Radiological Evaluation Criteria. Analyzes were performed with IBM SPSS 25.0 program and p<0.05 values ​​were considered statistically significant. Results: Nine (16.3%) of the patients who underwent a total knee prosthesis with ligament-cutting were male and 46 (83.7%) were female, and their ages were between 51 and 88 (mean, 66.7). Follow-up periods were between 2-60 months, with an average of 22.9 months. The number of patients who underwent unilateral knee prosthesis was 36, and the number of patients who underwent bilateral total knee prosthesis in the same session was 19. In the evaluation made according to the Knee Society Knee Prosthesis Evaluation Criteria, the knee score of the patients was 40 on average between 22and 60 before the operation, while the average knee score was 85 between 40 and 96 after the operation. The functional knee score was between 20 and 56 preoperatively, with an average of 40; It was found to be 85 on average between 20 and 100 after surgery. Revision surgeries were performed on septic ground in one patient and loosening findings on aseptic ground in one patient. Conclusion: In our study, it was stated that the total knee prosthesis that cuts the ligament has satisfactory results in terms of functionality and satisfaction if it is applied to the appropriate patient within the appropriate indication.